GP educators' understanding, experience and attitudes to teaching global health. Issue 1 (2nd January 2020) - Rees, Claire Patricia; Singh, Karishma; Knights, Felicity; Poppleton, Aaron
ABSTRACT: Global health is becoming increasingly relevant to GPs in the UK. A gap analysis revealed many global health capabilities are not currently in the GP curriculum. We undertook a survey of 240 GP educators to understand their views on global health and capacity to deliver global health teaching to GP trainees. This revealed a wide variation of experience, training, and confidence in global health teaching. It is important that the needs of GP trainers are taken into account when considering how global health training will be delivered